2007
DOI: 10.1007/s00595-006-3349-8
|View full text |Cite
|
Sign up to set email alerts
|

Solitary Nodal Recurrence in the Dorsal Area of the Thoracic Aorta After a Curative Resection of Esophageal Cancer: Report of Two Cases

Abstract: Although locoregional recurrence is often observed in the cervicothoracic area even after an esophagectomy with three-field lymph node dissection (3FL), recurrence in the mediastinal lymph nodes is relatively rare. We experienced two cases of solitary recurrence in a posterior mediastinal node (No 112-ao) after a curative resection for thoracic esophageal cancer. The lymph node recurrence was located in the connective tissue adjacent to the left posterior wall of the thoracic aorta, and thus could not have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…However, Nakagawa et al reported a case that underwent DTA dissection and died 10 months after the surgery owing to recurrence around the trachea [16] . Kaisaki et al reported two patients with dissection of lymph nodes in the DTA, who showed prolonged survival of 60 months and 12 months [17] . Hatooka et al reported two esophageal cancer patients with metastasis in the DTA, who died 19 months and 23 months after chemoradiotherapy, and another patient treated with neoadjuvant chemotherapy, followed by esophagectomy and dissection of lymph nodes in the DTA, who survived for 46 months after the operation without any recurrence [1] .…”
Section: Discussionmentioning
confidence: 99%
“…However, Nakagawa et al reported a case that underwent DTA dissection and died 10 months after the surgery owing to recurrence around the trachea [16] . Kaisaki et al reported two patients with dissection of lymph nodes in the DTA, who showed prolonged survival of 60 months and 12 months [17] . Hatooka et al reported two esophageal cancer patients with metastasis in the DTA, who died 19 months and 23 months after chemoradiotherapy, and another patient treated with neoadjuvant chemotherapy, followed by esophagectomy and dissection of lymph nodes in the DTA, who survived for 46 months after the operation without any recurrence [1] .…”
Section: Discussionmentioning
confidence: 99%
“…Recurrence after radical esophagectomy has been reported in the distant viscera, the locoregional area, and at multiple sites [8]. A report described two patients with solitary nodal recurrence in the dorsal area of the thoracic aorta after curative resection of esophageal cancer [9]. This area is therefore a site of tumor recurrence after curative surgery operation.…”
Section: Discussionmentioning
confidence: 99%
“…If recurrence is solitary or localized, which occurs in very few patients, a salvage operation is indicated. PDG-PET is useful in judging whether recurrence is solitary or multiple [8,9].…”
Section: Discussionmentioning
confidence: 99%